Praktik Dakwah Islam Di Media Digital dan Pengaruhnya - Intiha’ul Khiyaroh; Avif Alfiyah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2022)
Da'wah in digital media is a new phenomenon in da'wah activities in the era of society5.0 where the main component is humans who are able to create new value throughtechnological developments. Through social media that is in the hands of humans,anytime and anywhere can do da'wah with various content that can be produced bymad'u in preaching. The development of technology gave birth to an interestingphenomenon in today's social life, namely the rise of global culture and the tendency ofsociety to depend on the media. Da'wah in this millennial era must be able to makegood use of it, especially in the use of new media. If not, it will affect the morals andmorals of the millennial generation, which in fact they are looking for their identity. Inrelation to da'wah, the role of the media is very important and strategic in the deliveryof da'wah. The media is able to access information quickly and knows no boundaries ofspace and time.